Perancangan User Experience Aplikasi Mobile Learning menggunakan Metode Pendekatan Human-Centered Design (Studi Kasus: SD Negeri Pagerwojo Kabupaten Sidoarjo) - Yulia Salsah Sholihat; Agi Putra Kharisma; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Covid-19 pandemic has crippled all face-to-face activities that have an impact on all aspects of life, including aspects of education. Pagerwojo Primary School is one of several educational institutions that are affected by replacing its learning process with online school. However, the facilities provided by the school are not adequate. This can be seen from the media used for online learning processes which are through the WhatsApp messaging application which has several obstacles in the process of delivering learning.. From that problem, information technology is viewed as a solution that can accommodate various online schools. The study aims to design the user experience of a good mobile learning application using the Human-Centered Design approach (HCD), involving stakeholders and users in every step. The steps are determining the context of use, analyzing user needs, making design solutions, and evaluating design solutions. Evaluation of design solutions using usability testing and user experience. The results of the evaluation on the aspect of effectiveness produce a success rate of 100%, the efficiency aspect produces 0.03 goals/sec and the satisfaction aspect has an average value of 6.2. User experience testing the rating scale of attractiveness, efficiency, accuracy, stimulation, and novelty is in the excellent category and the clarity scale is in a good category. From the evaluation results, improvements were made to produce a better design solution.